Pengaruh Kepemimpinan Transformasional Kepala Sekolah, Budaya Kerja, dan Komitmen Organisasi terhadap Kinerja Guru di SMP Negeri Kecamatan Banjarmasin Utara - Gusti Salma Assyifa Balela; Aslamiah Aslamiah; Sulaiman Sulaiman (Universitas Cokroaminoto Palopo, 2024)
The aim of this research is to analyze the direct and indirect relationship between the principal's transformational leadership, work culture, and organizational commitment to teacher performance in North Banjarmasin District Public Middle Schools. The method used is quantitative descriptive research using a correlational path analysis model to analyze the relationship patterns between variables. The research population was 258 teachers from 8 Public Middle Schools in North Banjarmasin District and 157 respondents as iresearch isamples using the Proportionate Random Sampling technique. Data collection uses questionnairei instruments and data analysis uses descriptive analysis, classical assumptioni itesting, hypothesisi itesting, and ipath ianalysis. The results of this research show that the variable regression coefficient values ​​are positive numbers, such as the principal's transformational leadership variable (X1) with teacher performance (Y) of 0,197, work culture variable (X2) with teacher performance (Y) of 0,414, organizational commitment variable (Z) with teacher performance (Y) of 0,236, principal transformational leadership variable (X1) with organizational commitment (Z) of 0,510, work culture variable (X2) with organizational commitment (Z) of 0,544, the principal's transformational leadership variable (X1) with teacher performance (Y) through organizational commitment (Z) of 0,120, and the work culture variable (X2) with teacher performance (Y) through organizational commitment (Z) of 0,128. The conclusion of this research is that the relationship between the principal's transformational leadership variables, work culture, organizational commitment, and teacher performance at SMPN Negeri Banjarmasin Utara District obtained significant results. There is a partial direct relationship between the principal's transformational leadership, work culture, organizational commitment, and teacher performance. There is an indirect relationship between the principal's transformational leadership and work culture with teacher performance through organizational commitment.